Reduction of Residual Impurities in Homoepitaxial m‐Plane (101¯0) GaN by Using N2 Carrier Gas in Metalorganic Vapor Phase Epitaxy (Phys. Status Solidi RRL 8/2018). Issue 8 (8th August 2018) - Barry, Ousmane I; Lekhal, Kaddour; Bae, Si‐Young; Lee, Ho‐Jun; Pristovsek, Markus; Honda, Yoshio; Amano, Hiroshi
Abstract : Non‐polar ( m ‐plane) gallium nitride (GaN) materials are, unlike their polar ( c ‐plane) counterparts, free of polarizationinduced charges which make them very promising candidates for the development of high‐performance electronic devices including normally‐off enhancement mode transistors for safe power switching operation and very stable light emitters. However, the growth of m ‐plane GaN‐based device structures by metalorganic vapor phase epitaxy (MOVPE) commonly generates rough surface morphologies featuring four‐faceted pyramidal hillocks and also induces a high unintentional impurity uptake. These issues hinder further progress in device performance and reliability. In article no. 1800124, Ousmane I Barry et al. demonstrate that the synthesis of m ‐plane GaN crystals by MOVPE using nitrogen (N2 ) carrier gas, as opposed to conventional hydrogen (H2 ), can effectively reduce the residual impurity incorporation in addition to enhancing the surface morphology and mitigating the defect generation. This cost‐effective growth method enables to produce highquality homoepitaxial ( 10 1 ¯ 0 ) GaN films exhibiting optimal material properties which are highly desirable for developing next‐generation GaN devices.